Oil and natural gas rents and CO2 emissions nexus in MENA: spatial analysis - Mahmood, Haider; Saqib, Najia; Adow, Anass Hamadelneel; Abbas, Muzaffar (PeerJ, 2023)
Background Oil rents (OR) and natural gas rents (NGR) have significant contributions to the income of the Middle East and North Africa (MENA) economies and may increase emissions. Moreover, spatial autocorrelation is expected in carbon dioxide (CO2) emissions due to the geographically closed economies in the MENA region. Thus, we examine the impact of OR and NGR on CO2 emissions caring spatial dimensions and analyze the environmental Kuznets curve (EKC). Methods We apply the spatial Durbin model technique on the effects of OR, NGR, and economic growth on CO2 emissions in 17 MENA nations from 2000–2019, i.e., Algeria, Bahrain, Egypt, Iran, Iraq, Israel, Jordan, Kuwait, Libya, Morocco, Oman, Qatar, Saudi Arabia, Syria, Tunisia, the United Arab Emirates (UAE), and Yemen. Moreover, diagnostic tests are applied to reach the most appropriate spatial specification and to have the most robust results. Results The results disclose that CO2 emissions have spillovers and emissions of any country can damage the environment of neighboring countries. The EKC is corroborated with a turning point of 38,698 constant 2015 US dollars. Israel and Qatar are in 2nd phase of the EKC, and 15 MENA economies are in 1st stage. Thus, the economic expansion of most economies has ecological concerns. The effect of natural gas rents is found statistically insignificant. Oil rents have minute negative effects on emissions of local economies with an elasticity coefficient of −0.2117. Nevertheless, these have a positive indirect effect with an elasticity coefficient of 0.5328. Thus, the net effect of oil rents is positive. One percent increase in oil rents could accelerate 0.3211% of emissions. Thus, we suggest the MENA countries reduce reliance on oil rents in their income to avoid the negative environmental effects of the oil sector.
Keywords: Oil rent; Natural gas rents; CO2 emissions; Spillovers; The MENA region